GISAID-Clade and Pangolin Lineage Wise Distribution Patterns of COVID-19 Virus, in India - Halder, Ankur; Islam, Sk. Saruk; Ali, Sk. Nasim; Hossain, Mehebub Sarwar; Midya, Sujoy; Saadi, Sk. Md. Abu Imam (Current Overview on Disease and Health Research Vol. 6, 2022)
Transmissible coronavirus (SARS-CoV-2), created a universal pandemic situation since the last of 2019 and has outspread widely until now. Where India was the second most affected country and 3rd in mortality rate around the world. At present, we analyzed the diversity of SARS-CoV-2 viral genomes in India to know the evolutionary patterns of viruses in the country through their pangolin lineage and GISAID-Clade. We extracted a total of 2189 full-length SARS-CoV-2 viral genomes from various states of India from the EpiCov repository of the GISAID initiative on 12 June 2020. We observed that a total of 66 pangolin lineage and 9 GISAID-Clade were placed in Indian territory. The most dominant lineages and clades in India as predicted by Pangolin lineage and GISAID-Clade genome sequences were B1, B6, B1.1.7, B.1.617.2, B1.36 and B1.1.306, G and GR, respectively. Out of fifteen states of India, maximum lineage diversity i.e., 63.64% of lineage was found in Maharashtra; also, all types of GISAID-Clades found in India were also present in Maharashtra. Whereas, the lowest lineage and GISAID-Clade diversity were observed in West Bengal. Because the pandemic is still emerging, the observation needs to be monitored.